MANAJEMEN KURIKULUM PENDIDIKAN KETERAMPILAN BAGI ANAK BERKEBUTUHAN KHUSUS (TUNARUNGU) DI SLB MA’ARIF MUNTILAN - Muslimah, Muslimah (Educational Management, 2012)
Abstract: The objectives of the study were to describe and to analyze of the management curriculum of the education skills for the special needs children (deaf) at SLB Ma’arif Muntilan. The data collection was accomplished by using the interviews, the observation and the library research. The results of the study showed that (1) the planning of the education skills curriculum was started by conducting need analysis, curriculum objectives and the curriculum content design, and evaluation, (2) the organization of the education skills curriculum was divided into the organization of human resources and infrastructures, the arrangement of the school’s subjects and the time allocation, (3) the implementation of the education skills curriculum was executed by preparing the syllabus, the annual programs, the semester’s programs and the lesson plans, and last but not least the evaluation of the school’s activities, (4) the evaluation of the education skill curriculum was assessed by reviewing the the objectives, the functions, and the steps of the evaluations itself. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis manajemen kurikulum pendidikan keterampilan bagi anak berkebutuhan khusus (tunarungu) di SLB Ma’arif Muntilan. Data diperoleh dengan cara wawancara, observasi dan dokumentasi. Hasil penelitian menunjukkan bahwa (1) Perencanaan kurikulum pendidikan keterampilan dimulai dari identifikasi kebutuhan, perumusan tujuan kurikulum, perumusan isi kurikulum dan penentuan evaluasi (2) Pengorganisasian kurikulum pendidikan keterampilan meliputi pengorganisasian sumber daya manusia dan sarana prasarana, pengaturan materi pelajaran serta pengaturan waktu (3) Pelaksanaan kurikulum pendidikan keterampilan dimulai dengan pembuatan silabus, program tahunan, program semesteran dan Rencana Pelaksanaan Pembelajaran, pelaksanaan pembelajaran serta evaluasi pelaksanaan pembelajaran (4) Evaluasi terhadap kurikulum pendidikan keterampilan bagi anak berkebutuhan khusus meliputi tujuan, fungsi dan bentuk atau cara evaluasi.